CALCULATION OF STRUCTURE RETAINING WALLS OF LAND FOR HANDLING LANDSLIDES SEGMENT 1 VILLAGE ROAD MARGOMULYO KABUPATEN KUTAI KARTANEGARA - LANI, KAE (KURVA S JURNAL MAHASISWA, 2014)
Margomulyo Vilage area, District Loa Janan, a vilage located in theDistrict Loa Jana ,but in the vilage is an area that is prone to landslides, this isdue to topographical conditons in the area in the form of hily areas, mining andagricultural region. Lack of suporting vegetation bufer zones rainwater andmake this area very prone to landslides in the event of rain, so at some pointalong the river have sen the potential for erosion and landslide potential, whichrequires extra care and handling of fast, responsive and acurate prior to theocurence of landslides as a whole in cros section of the riverbank.Handling avalanches due to erosion of the river banks, of course, requirethe existence of analysis and technical studie ,detailed and comprehensive, so itcan produce a design that is apropriate and efective in order to conform withthe original purpose of the handling of the avalanche can be achieved From thecalculation results can be concluded that ,dimensional wal pehanan high groundis 3 meters and a width of 1 meter, 1 meter thick plate with a length of 10 metersper segment review. Secure the stabilty of a retaining wal to bolster howeverafect he shear, so that he necesary foundation piles with aditonal bracing tothe pile group to rigidify the structure of the wals and the pile.